Learning Results and Online Learning Activities of Accounting Students During the Covid-19 Pandemic - Khanti Listya (Jurnal Scientia, 2021)
The Covid-19 pandemic that occurred greatly affected various activities in various fields, one of which was education. One of the most felt impacts is the change in the education system from face-to-face to online system. This study aims to determine accounting students' learning outcomes and online learning activities during the Covid-19 pandemic at Universitas Al Azhar. The subjects in this study were students majoring in accounting, amounting to 54 people. In this study, researchers surveyed to collect data. In addition to conducting surveys, researchers also made observations during online learning to find out the learning activities carried out by students. From the results of the study and observation, the next researcher conducted interviews with the research subjects. Based on the study results, it is known that online learning carried out by Accounting students at Universitas Al Azhar uses various supporting applications such as WhatsApp, Google Classroom, Google Meet, and Zoom. Online learning outcomes are assessed using the GPA as a reference for assessment. Based on the GPA obtained by students, it is known that there was an increase in student learning outcomes wherein the even semester of the 2019/2020 Academic Year the average GPA was 3.44 to 3.51 in the odd semester of the 2019/2020 Academic Year. In contrast to student learning outcomes which have increased, online learning activities for Accounting students during the Covid-19 Pandemic at the University are just the opposite. From the observations, it was found that the learning activities of accounting students during the Covid-19 pandemic at Universitas Al Azhar were 9 students in the active category, 15 students in the moderately active, 11 in the less active, and 19 students in the inactive. Furthermore, based on observations, it is known that the online learning activities of accounting students during the Covid-19 pandemic at Universitas Al Azhar have not been suitable, where the average student activity score is less than 23, which is 16.61. Based on the moderate activity of 16.61, it is known that the learning activities of Accounting students at Al Azhar University during the Covid-19 pandemic were less active. Based on the interviews, it is known that students, online learning activities of Accounting students experience many obstacles, including the difficulty of the internet network, limited internet quota, and lack of facilities such as laptops and computers. With these many obstacles, of course, it will affect student activities in following online learning. In addition, accounting students at Universitas Al Azhar focus more on listening to what the lecturers say in the online learning process. Students do not ask a lot of questions or provide feedback when learning activities take place. Learning activities tend to be one-way, where the lecturer is the only source in the online learning process.